PENYAKIT PADA TANAMAN BAWANG MERAH (Allium ascalonicum L.) YANG DISEBABKAN OLEH CENDAWAN DI PERTANAMAN RAKYAT DAERAH BREBES - Eka Widiyarti; Purnomowati Purnomowati; Eddy Tri Sucianto (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
Shallot (Allium ascalonicum L.) is one of the horticultural commodities which highly developed and cultivated in Brebes. Brebes contributed to fulfill up to 23% to the national needs. But, its production decreased 0.87% annually. The intensification of shallot production faced many problems, especially the diseases caused by the pathogenic fungi causing the low crop production. We conducted this study during the period of May–October 2012. The purpose of this study was to find out the type of pathogenic fungi and to determine the diseases including the dominant disease on shallot crops in Brebes. The research was a survey, and a diagonally purposive sampling technique applied at five different locations. We identified the plant diseases based on identification key books of the Penyakit-Penyakit Tanaman Hortikultura and the Plant Disease Handbook as references. We described the diseases according to the signs and symptoms followed by the isolation of pathogenic fungi that cause disease. The pathogenic fungi identification was completed using the Illustrated Genera of Imperfect Fungi, the Compedium of Soil Fungi, and the Pengenalan Kapang Tropik Umum as references. This study found three diseases in shallot crops, i.e., Fusarium tuber rot, Aspergillus tuber rot and Curvularia leaf spot. The dominant shallot crop disease was the Curvularia leaf spot.